A Review Of The Performance Of The Electrowinning Systems Within The Newcrest Group Of Operating Mines - Mike Costello (Society for Mining, Metallurgy & Exploration, 1995)
The gold mines operating within the Newcrest Group, Boddington (20% owned), New Celebration, Ora Banda and Telfer, have accumulated many years of operating experience. Cell designs and operating methods include both steel wool and woven stainless steel and plating practices cover electrowin, electrorefine, normal' recirculation and pass out modes. Besides gold the solutions contain reasonable quantities of silver, copper and nickel.